The Effects of Diabetes Exercise on Blood Glucose Levels in Patients With Type II Diabetes Mellitus at Budi Rahayu Hospital in Pekalongan - Fransisca Andina Suci Wardani; Menik Kustriyani (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
Nonpharmacological interventions are critical in managing metabolic trajectories and mitigating vascular complications in type II diabetes mellitus. This study evaluated the clinical efficacy of structured morning exercise protocols on blood glucose stabilization among patients at Budi Rahayu Hospital. A clinical assessment tracked baseline and postregimen glycemic shifts during strategic morning windows, analyzing systemic physiological covariates including muscle mass degradation, dietary framework adherence, and pharmacological compliance. The implementation of thirtyminute exercise sessions generated significant net glycemic reductions ranging from 60 to 115 milligrams per deciliter. Absolute glucose clearance correlated strongly with higher initial hyperglycemia, though final metabolic stabilization depended heavily on baseline values. Agerelated muscle mass decline restricted optimal insulinindependent glucose uptake, whereas strict adherence to medication and the structured threeJ dietary principles enhanced longterm therapeutic outcomes. Structured light exercise serves as a highly effective, costefficient, and protective nursing intervention that optimizes metabolic clearance and improves patient selfcare behaviors when combined with comprehensive lifestyle modifications.